ee A: 1 B: 7 C: 4
ee A: 1 B: 7 C: 4
函数y=x²-1的值域是( ) A: {y|y≥1} B: {y|y≥-1} C: {y|y≤1} D: {y|y≤-1}
函数y=x²-1的值域是( ) A: {y|y≥1} B: {y|y≥-1} C: {y|y≤1} D: {y|y≤-1}
【单选题】对任意实数x 1 , y 1 , x 2 , y 2 , x 1 < x 2 , y 1 < y 2 , 分布函数P{x 1 <X≤x 2 , y 1 <Y≤y 2 }=? A. F(x 2 , y 2 )+ F(x 1 , y 1 )+ F(x 1 , y 2 )+ F(x 2 , y 1 ) B. F(x 2 , y 2 )- F(x 1 , y 1 )+ F(x 1 , y 2 )- F(x 2 , y 1 ) C. F(x 2 , y 2 )+ F(x 1 , y 1 )- F(x 1 , y 2 )- F(x 2 , y 1 ) D. F(x 2 , y 2 )- F(x 1 , y 1 )- F(x 1 , y 2 )+ F(x 2 , y 1 )
【单选题】对任意实数x 1 , y 1 , x 2 , y 2 , x 1 < x 2 , y 1 < y 2 , 分布函数P{x 1 <X≤x 2 , y 1 <Y≤y 2 }=? A. F(x 2 , y 2 )+ F(x 1 , y 1 )+ F(x 1 , y 2 )+ F(x 2 , y 1 ) B. F(x 2 , y 2 )- F(x 1 , y 1 )+ F(x 1 , y 2 )- F(x 2 , y 1 ) C. F(x 2 , y 2 )+ F(x 1 , y 1 )- F(x 1 , y 2 )- F(x 2 , y 1 ) D. F(x 2 , y 2 )- F(x 1 , y 1 )- F(x 1 , y 2 )+ F(x 2 , y 1 )
下列语句与y=(x>;0?1:x<;0?-1:0);语句功能相同是( ) A: if (x) if(x>;0) y=1; else if(x<;0) y=-1;else y=0; B: y=-1; if(x>;0) y=1; else y=-1; C: if (x>;0) y=1; else if(x<;0) y=-1; else y=0; D: y=0; if(x>;=0) y=1;else if(x==0) y=0; else y=-1;
下列语句与y=(x>;0?1:x<;0?-1:0);语句功能相同是( ) A: if (x) if(x>;0) y=1; else if(x<;0) y=-1;else y=0; B: y=-1; if(x>;0) y=1; else y=-1; C: if (x>;0) y=1; else if(x<;0) y=-1; else y=0; D: y=0; if(x>;=0) y=1;else if(x==0) y=0; else y=-1;
随机变量X ~ N ( 0 , 1 ),Y ~ N ( 1, 4 ),且相关系数[img=61x22]1802f2bde8cad19.png[/img],则( ). A: P{ Y = -2X -1} = 1 B: P{ Y = 2X -1} = 1 C: P{ Y = -2X + 1} = 1 D: P{ Y = 2X + 1} = 1
随机变量X ~ N ( 0 , 1 ),Y ~ N ( 1, 4 ),且相关系数[img=61x22]1802f2bde8cad19.png[/img],则( ). A: P{ Y = -2X -1} = 1 B: P{ Y = 2X -1} = 1 C: P{ Y = -2X + 1} = 1 D: P{ Y = 2X + 1} = 1
随机变量X ~ N ( 0 , 1 ),Y ~ N ( 1, 4 ),且相关系数[img=61x22]1803c07c2f6d74e.png[/img],则( ). A: P{ Y = -2X -1} = 1 B: P{ Y = 2X -1} = 1 C: P{ Y = -2X + 1} = 1 D: P{ Y = 2X + 1} = 1
随机变量X ~ N ( 0 , 1 ),Y ~ N ( 1, 4 ),且相关系数[img=61x22]1803c07c2f6d74e.png[/img],则( ). A: P{ Y = -2X -1} = 1 B: P{ Y = 2X -1} = 1 C: P{ Y = -2X + 1} = 1 D: P{ Y = 2X + 1} = 1
随机变量X ~ N ( 0 , 1 ),Y ~ N ( 1, 4 ),且相关系数[img=61x22]1802f2bc50655c0.png[/img],则( ). A: P{ Y = -2X -1} = 1 B: P{ Y = 2X -1} = 1 C: P{ Y = -2X + 1} = 1 D: P{ Y = 2X + 1} = 1
随机变量X ~ N ( 0 , 1 ),Y ~ N ( 1, 4 ),且相关系数[img=61x22]1802f2bc50655c0.png[/img],则( ). A: P{ Y = -2X -1} = 1 B: P{ Y = 2X -1} = 1 C: P{ Y = -2X + 1} = 1 D: P{ Y = 2X + 1} = 1
随机变量X ~ N ( 0 , 1 ),Y ~ N ( 0 , 1 ),且相关系数[img=61x22]1803395efc2083a.png[/img],则( ). A: P{ Y = -2X -1} = 1 B: P{ Y = 2X -1} = 1 C: P{ Y = -2X + 1} = 1 D: P{ Y = 2X + 1} = 1
随机变量X ~ N ( 0 , 1 ),Y ~ N ( 0 , 1 ),且相关系数[img=61x22]1803395efc2083a.png[/img],则( ). A: P{ Y = -2X -1} = 1 B: P{ Y = 2X -1} = 1 C: P{ Y = -2X + 1} = 1 D: P{ Y = 2X + 1} = 1
随机变量X ~ N ( 0 , 1 ),Y ~ N ( 0 , 1 ),且相关系数[img=61x22]180390b1ffcc8de.png[/img],则( ). A: P{ Y = -2X -1} = 1 B: P{ Y = 2X -1} = 1 C: P{ Y = -2X + 1} = 1 D: P{ Y = 2X + 1} = 1
随机变量X ~ N ( 0 , 1 ),Y ~ N ( 0 , 1 ),且相关系数[img=61x22]180390b1ffcc8de.png[/img],则( ). A: P{ Y = -2X -1} = 1 B: P{ Y = 2X -1} = 1 C: P{ Y = -2X + 1} = 1 D: P{ Y = 2X + 1} = 1
随机变量X ~ N ( 0 , 1 ),Y ~ N ( 1, 4 ),且相关系数[img=61x22]1803a74e43c340e.png[/img],则( ). A: P{ Y = -2X -1} = 1 B: P{ Y = 2X -1} = 1 C: P{ Y = -2X + 1} = 1 D: P{ Y = 2X + 1} = 1
随机变量X ~ N ( 0 , 1 ),Y ~ N ( 1, 4 ),且相关系数[img=61x22]1803a74e43c340e.png[/img],则( ). A: P{ Y = -2X -1} = 1 B: P{ Y = 2X -1} = 1 C: P{ Y = -2X + 1} = 1 D: P{ Y = 2X + 1} = 1